'Maybe it is prejudice … but it is NOT racism': Negotiating racism in discussion forums about Gypsies. (January 2014) - Goodman, Simon; Rowe, Lottie
This article addresses the ways in which opposition towards Gypsies is debated, with particular regard to whether or not this opposition constitutes racism or prejudice towards a group shown to be vulnerable and subject to discrimination. A discursive analysis of a corpus of internet discussion forums about Gypsies in the UK is undertaken. The analysis demonstrates that opposition towards Gypsies can be presented as racist; however, such accusations are met with criticism so that writers become accountable for making them. While writers do go to rhetorical lengths to dissociate themselves from being presented as racist, there is nevertheless an acceptance that opposition to Gypsies may constitute prejudice. This prejudice is presented as an inevitable result of Gypsies' behaviour and, of particular note, appears to be deemed acceptable. The implications of this finding for the discursive literature on taboos against, and denials of, racism are discussed.